Amelia Bedelia Goes Camping - Parish, Peggy (The Hearst Corporation, 1986)
As always, Amelia Bedelia follows exactly the instructions given to her on a camping trip, including pitching a tent and rowing boats.
Keywords: Juvenile literature-Fiction